Positive electrode composition, positive electrode, and secondary battery
By using a first positive electrode active material in the form of a single particle and a second positive electrode active material with high particle strength in the positive electrode of the secondary battery, combined with a binder and a conductive material, the high negative electrode of the silicon active material in the secondary battery is solved. The initial irreversible capacity and gas generation problems have achieved improvements in high energy density and fast charging performance.
Patent Information
- Application Number
- CN202380049175.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-25
- Filing Date
- 2023-09-26
- Publication Date
- 2025-02-07
AI Technical Summary
When using the negative electrode of a silicon-based active material in the existing secondary batteries, there are problems of high initial irreversible capacity and reaction with the electrolyte solution to generate gas.
Using the first positive electrode active material in the form of a single particle and the second positive electrode active material with a particle size greater than the first positive electrode active material, combined with the adhesive and the conductive material, an efficient positive electrode composition is formed to increase the energy density and roll pressure of the electrode. density.
The electrode with high energy density is achieved, which reduces particle rupture and fine powder generation during rolling, improves the problem of gas reaction with the electrolyte solution, and improves the fast charging performance of the battery.
Smart Images

Figure BDA0005203423950000141 
Figure BDA0005203423950000142
Abstract
Description
Technical Field
[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0125359 filed on September 30, 2022, in the Korean Intellectual Property Office and Korean Patent Application No. 10-2023-0127942 filed on September 25, 2023, in the Korean Intellectual Property Office, the entire contents of which are incorporated herein by reference.
[0002] The invention relates to a positive electrode composition, a positive electrode and a secondary battery. Background Art
[0003] Secondary batteries are commonly used not only in portable devices but also in electric vehicles (EVs) or hybrid electric vehicles (HEVs) driven by an electric driving source.
[0004] Secondary batteries are drawing attention as a new energy source that improves eco-friendliness and energy efficiency because a primary advantage is that the use of fossil fuels is significantly reduced, and a second advantage is that the use of energy does not generate byproducts.
[0005] Typically, a secondary battery includes a positive electrode, a negative electrode, a separator and an electrolyte disposed between the positive electrode and the negative electrode, etc. In addition, electrodes such as the positive electrode and the negative electrode may have an electrode active material layer disposed on a current collector. As the use of secondary batteries increases, various battery performances are required. For example, in order to develop high-capacity batteries, attempts are being made to apply silicon-based active materials to the negative electrode. However, silicon-based active materials have the main problem of high initial irreversibility. In order to improve battery performance, attempts are being made to adjust the components of the positive or negative electrode or to add additives. However, the wrong combination of materials may have an adverse effect on the performance of the final battery. Therefore, it is necessary to study the combination of positive or negative electrode materials to improve battery performance. Summary of the invention
[0006] Technical issues
[0007] The present invention aims to provide a positive electrode composition, a positive electrode and a secondary battery containing the same, wherein the positive electrode composition can not only provide the irreversible capacity of the negative electrode when used with a negative electrode using a silicon-based active material, but also realize an electrode with high energy density and improve the problem of gas generation due to reaction with an electrolyte solution.
[0008] Technical Solution
[0009] An exemplary embodiment of the present invention provides a positive electrode composition comprising: a first positive electrode active material in the form of a single particle; a second positive electrode active material having a particle size larger than that of the first positive electrode active material and a particle strength of 150 MPa or more; a binder; and a conductive material.
[0010] Another exemplary embodiment of the present invention provides a positive electrode for a secondary battery, including: a current collector; and a positive electrode active material layer disposed on the current collector and including the positive electrode composition of the above exemplary embodiment.
[0011] Still another exemplary embodiment of the present invention provides a secondary battery including the positive electrode of the above exemplary embodiment, a negative electrode, and a separator.
[0012] According to yet another exemplary embodiment of the present invention, the negative electrode includes a silicon-based active material.
[0013] Beneficial effects
[0014] According to the exemplary embodiment described in this specification, a first positive electrode active material in the form of a single particle and a second positive electrode active material having a high particle strength are used as positive electrode active materials, so that not only high density but also low efficiency can be achieved. Specifically, under low efficiency characteristics, when used with a negative electrode using a silicon-based active material, the irreversible capacity of the negative electrode can be provided. In addition, the first positive electrode active material and the second positive electrode active material can suppress the generation of fine powder due to particle breakage during rolling, thereby preventing an increase in specific surface area and improving the problem of gas generation due to reaction with an electrolyte solution. In addition, since the problems in the rolling process can be improved as described above, the rolling density can be increased, thereby achieving not only high energy density, but also reducing the thickness of the positive electrode to improve fast charging performance. DETAILED DESCRIPTION
[0015] Hereinafter, in order to better understand the present invention, the present invention will be described in more detail. The present invention can be implemented in various different forms and is not limited to the exemplary embodiments described herein. The terms or words used throughout the specification and claims should not be interpreted as limited to their ordinary or dictionary meanings, but should be interpreted as having meanings and concepts consistent with the technical ideas of the present invention based on the concept that the inventor can appropriately define the words or terms to best explain the principles of the present invention.
[0016] It should also be understood that when used in this specification, the terms "includes", "comprising" or "having" specify the presence of stated features, integers, steps, constituent elements and / or combinations thereof, but do not exclude the presence or addition of one or more other features, integers, steps, constituent elements and / or combinations thereof.
[0017] In addition, it should be understood that when an element such as a layer is referred to as being "on" another element, it can be "directly" "on" the other element, or intervening elements may also be present. In contrast, when an element is referred to as being "directly" "on" another element, there are no intervening elements. Furthermore, when an element is referred to as being "on" a reference portion, the element is located above or below the reference portion, and does not necessarily mean that the element is located "above" or "on" in a direction opposite to gravity.
[0018] In this specification, particle size refers to the particle size represented by D 50 The average particle size. 50 It can be defined as the particle size at 50% of the particle size distribution and can be measured using a laser diffraction method. For example, the average particle size (D 50 ) may include dispersing particles of a positive electrode active material in a dispersion medium, introducing the dispersion into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), irradiating the dispersion with ultrasonic waves of about 28 kHz at an output of 60 W, and then calculating an average particle size (D ) corresponding to 50% of the cumulative volume in the measuring device. 50 ).
[0019] In the present specification, “primary particles” refer to particles that appear to have no grain boundaries when observed at a field of view of 5000 to 20000 times using a scanning electron microscope.
[0020] In the present specification, "secondary particles" refer to particles formed by agglomeration of primary particles.
[0021] In this specification, single particle is a term used to distinguish it from positive electrode active material particles in the form of secondary particles produced by agglomeration of tens to hundreds of primary particles generally used in the related art, and is a concept including single particles composed of one primary particle and agglomerated particles of 10 or less primary particles.
[0022] In the present specification, when "particles" are mentioned, it may refer to any one or all of single particles, secondary particles, and primary particles.
[0023] The cathode composition of the exemplary embodiment of the present specification includes: a first cathode active material in a single particle form; a second cathode active material having a larger particle size than the first cathode active material and a particle strength of 150 MPa or more; a binder; and a conductive material.
[0024] In this specification, for convenience, the first positive electrode active material in the form of a single particle may be referred to as a small-particle positive electrode active material, and the second positive electrode active material having a particle size larger than that of the first positive electrode active material and a particle strength of 150 MPa or more may be referred to as a large-particle positive electrode active material.
[0025] In the above exemplary embodiment, by using a single particle form as a small particle size positive electrode active material, the lithium path can be extended to reduce efficiency. In addition, by applying a single particle with excellent rolling density, a high-density electrode can be achieved, and by applying a single particle with excellent tap density, the rolling ratio can be improved to suppress the generation of fine powder due to particle rupture. According to one example, the tap density of the first positive electrode active material is 2 g / cc or more, for example, 2 g / cc or more and 30 g / cc or less. According to one example, the rolling density of the first positive electrode active material is 3 g / cc or more, for example, 3 g / cc or more and 30 g / cc or less.
[0026] The tap density is the apparent density of particles obtained by vibration under specific conditions and can be measured using a tap density tester (KYT-5000, Seishin). The roll density can be measured using a powder resistance characteristic device HPRM-1000 (HANTECH CO.) at 2000 kgf / cm 2 The force during rolling is measured by the rolling density.
[0027] In the above exemplary embodiment, the particle size of the second positive electrode active material is larger than the particle size of the first positive electrode active material and the particle strength is 150 MPa or more. The particle strength of the second positive electrode active material may preferably be 180 MPa or more. The higher the particle strength of the second positive electrode active material, the more advantageous it is. However, for example, the particle strength may be 600 MPa or less.
[0028] The particle strength refers to the force at which the particles break when compression force is increased after the particles are placed on a plate, and can be measured using a micro compression tester (Shimadzu, MCT-W500).
[0029] According to an exemplary embodiment, the particle strength of the first cathode active material is 150 MPa or more, preferably 180 MPa or more and less than 250 MPa. If the particle strength of the first cathode active material is 250 MPa or more, rolling characteristics may be deteriorated.
[0030] According to an exemplary embodiment, the second positive electrode active material may be in the form of secondary particles, in which case the particle size of the secondary particles is larger than the particle size of the single particle of the first positive electrode active material. Even when the second positive electrode active material is a secondary particle, as described above, the particle strength is 150 MPa or more, so even when rolling an electrode mixed with the first positive electrode active material in the form of a single particle, particle breakage is reduced and the generation of fine powder is suppressed, thereby reducing the generation of gas. When manufacturing the positive electrode active material, the particle strength of the large particle size positive electrode active material can be adjusted by controlling the firing conditions such as firing time or temperature.
[0031] According to an exemplary embodiment, D of the first positive electrode active material 50 The D of the second positive electrode active material may be 1 μm to 10 μm. 50 The second positive electrode active material may have a particle size that is 3 μm to 15 μm, for example, 5 μm to 10 μm larger than the first positive electrode active material. When the particle size difference between the first and second positive electrode active materials is 3 μm to 15 μm, particle crushing is improved, which is conducive to improving the generation of fine powder and gas.
[0032] According to an exemplary embodiment, the weight ratio of the first positive electrode active material to the second positive electrode active material may be 1:9 to 9:1, specifically 3:7 to 7:3. In particular, when the content ratio of the first and second positive electrode active materials is 3:7 to 7:3, the rolling characteristics of the electrode are improved, which is conducive to achieving a high-density electrode.
[0033] According to an exemplary embodiment, the first positive electrode active material and the second positive electrode active material may each include a lithium composite transition metal compound including nickel (Ni) and cobalt (Co). The lithium composite transition metal compound may further include at least one of manganese and aluminum. The lithium composite transition metal compound may include 80 mol% or more, for example, 80 mol% or more and less than 100 mol% of nickel in a metal other than lithium. For example, the lithium composite transition metal compound may be composed of Li a Ni (1-x-y) Co x M1 y M2 w A positive electrode active material represented by O2 (1.0≤a≤1.5, 0≤x≤0.2, 0≤y≤0.2, 0≤w≤0.1, 0≤x+y≤0.2, M1 is at least one metal selected from Mn or Al, and M2 is one or more metal elements selected from the group consisting of Ba, Ca, Zr, Ti, Mg, Ta, Nb and Mo).
[0034] According to an exemplary embodiment, the first positive electrode active material and / or the second positive electrode active material may further include a cobalt oxide layer disposed on at least a portion of its surface. The cobalt raw material of the cobalt oxide layer may include lithium cobalt oxide by reacting with the residual lithium on the surface of the active material. In this case, the effect of reducing the residual lithium on the surface of the active material can be exhibited, and the effect of improving the output due to the excellent lithium ion conductivity of the lithium cobalt oxide can be exhibited. In addition, the cobalt oxide layer is present on the surface of the active material, so that the side reaction with the electrolyte solution can be reduced.
[0035] According to another exemplary embodiment of the present specification, the positive electrode binder can be used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material particles and the positive electrode current collector. For positive electrode binders, those known in the art can be used. Its non-limiting examples may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, and any one of them or a mixture of two or more thereof can be used.
[0036] The content of the positive electrode binder may be 0.1 parts by weight to 50 parts by weight, for example, preferably 0.3 parts by weight to 35 parts by weight, and more preferably 0.5 parts by weight to 20 parts by weight, based on 100 parts by weight of the positive electrode active material layer.
[0037] The conductive material contained in the positive electrode active material layer is used to impart conductivity to the electrode, and can be used without particular limitation as long as the conductive material has electronic conductivity without causing chemical changes in the battery. Specific examples may include: graphite, such as natural graphite and artificial graphite; carbon-based materials, such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, etc., and any one of them or a mixture of two or more thereof may be used.
[0038] Specifically, in an exemplary embodiment, the conductive material may include one or more of single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT). Based on 100 parts by weight of the composition for the positive electrode active material layer, the content of the conductive material may be 0.1 parts by weight or more and 2 parts by weight or less, for example, preferably 0.3 parts by weight or more and 1.5 parts by weight or less, and more preferably 0.5 parts by weight or more and 1.2 parts by weight or less.
[0039] According to another exemplary embodiment of the present specification, a secondary battery positive electrode is provided, comprising: a current collector; and a positive electrode active material layer disposed on the current collector and comprising the positive electrode composition. The thickness of the positive electrode active material layer may be 20 μm or more and 500 μm or less.
[0040] According to an exemplary embodiment, based on 100% by volume of the positive electrode active material layer, the fine powder having a particle size of 1 μm or less in the positive electrode active material layer is 5% by volume or less, preferably 3% by volume or less, and more preferably 1% by volume or less. The content of fine powder in the positive electrode active material layer can be measured by heat treating the rolled electrode at 500° C. in an air atmosphere for 5 hours to remove the conductive material and the binder, and obtaining only the positive electrode active material and subjecting it to a laser diffraction method. For example, the content can be measured by dispersing a lithium composite transition metal oxide powder or a positive electrode active material powder in a dispersion medium, introducing the dispersion into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), irradiating the dispersion with an ultrasonic wave of about 28 kHz with an output of 60 W, obtaining a volume cumulative particle size distribution diagram, and then calculating the cumulative volume below 1 μm.
[0041] In 100 parts by weight of the positive electrode active material layer, the content of the positive electrode active material can be more than 80 parts by weight and less than 99.9 parts by weight, preferably more than 90 parts by weight and less than 99.9 parts by weight, more preferably more than 95 parts by weight and less than 99.9 parts by weight, and most preferably more than 98 parts by weight and less than 99.9 parts by weight.
[0042] There is no particular limitation on the positive electrode current collector, as long as it has conductivity without causing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., etc., can be used. In addition, the positive electrode current collector may generally have a thickness of 1 μm to 500 μm, and the surface of the current collector may be formed with microscopic concavoconvex objects to enhance the adhesion of the positive electrode active material. For example, the positive electrode current collector may be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0043] Another exemplary embodiment of the present specification provides a secondary battery including the positive electrode, negative electrode, and separator of the above exemplary embodiment.
[0044] The negative electrode may include a current collector and a negative electrode active material layer provided on the current collector.
[0045] According to an exemplary embodiment, the negative electrode contains a silicon-based active material.
[0046] Containing SiO x (0 ≤ x < 2) As the active material of the silicon-based active material may be a silicon-based composite particle containing SiO x (0 < x < 2) and pores.
[0047] SiO x (0 < x < 2) corresponds to the matrix in the silicon-based composite particle. SiO x (0 < x < 2) may be in the form including Si and SiO2, and Si may also form a phase. That is, x corresponds to the number ratio of O to Si contained in SiO x (0 < x < 2). When the silicon-based composite particle includes SiO x (0 < x < 2), the discharge capacity of the secondary battery can be improved.
[0048] The silicon-based composite particle may further include at least one of a Mg compound and a Li compound. The Mg compound and the Li compound may correspond to the matrix in the silicon-based composite particle.
[0049] The Mg compound and / or the Li compound may be present in SiO x (0 < x < 2) and / or on the surface of SiO x (0 < x < 2). Through the Mg compound and / or the Li compound, the initial efficiency of the battery can be improved.
[0050] The Mg compound may include at least one selected from the group consisting of Mg silicate, Mg silicide, and Mg oxide. The Mg silicate may include at least one of Mg2SiO4 and MgSiO3. The Mg silicide may include Mg2Si. The Mg oxide may include MgO.
[0051] In an exemplary embodiment of the present specification, based on a total of 100% by weight of the silicon-based active material, the content of the Mg element may be 0.1% to 20% by weight, or 0.1% to 10% by weight. Specifically, the content of the Mg element may be 0.5% to 8% by weight or 0.8% to 4% by weight. When the above range is satisfied, the Mg compound can be included in the silicon-based active material in an appropriate content, so that the volume change of the silicon-based active material during the charge and discharge of the battery can be easily suppressed, and the discharge capacity and initial efficiency of the battery can be improved.
[0052] The Li compound may include at least one selected from the group consisting of lithium silicate, lithium silicide, and lithium oxide. The lithium silicate may include at least one of Li2SiO3, Li4SiO4, and Li2Si2O5. The lithium silicide may include Li7Si2. The lithium oxide may include Li2O.
[0053] In an exemplary embodiment of the present invention, the Li compound may include the form of lithium silicate. Lithium silicate is represented by Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and can be divided into crystalline lithium silicate and amorphous lithium silicate. The crystalline lithium silicate may exist in the silicon-based composite particles in the form of at least one lithium silicate selected from the group consisting of Li2SiO3, Li4SiO4, and Li2Si2O5, and the amorphous lithium silicate may be in the form of Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5). However, the present invention is not limited thereto.
[0054] In an exemplary embodiment of the present specification, based on a total of 100% by weight of the silicon-based active material, the content of the Li element may be 0.1% to 20% by weight, or 0.1% to 10% by weight. Specifically, the content of the Li element may be 0.5% to 8% by weight, and more specifically 0.5% to 4% by weight. When the above range is satisfied, the Li compound can be included in the silicon-based active material in an appropriate content, so that the volume change of the negative electrode active material during the charge and discharge of the battery can be easily suppressed, and the discharge capacity and initial efficiency of the battery can be improved.
[0055] The content of Mg element or Li element can be confirmed by ICP analysis. For ICP analysis, a predetermined amount (about 0.01g) of negative electrode active material is accurately taken, then transferred to a platinum crucible and completely decomposed on a hot plate by adding nitric acid, hydrofluoric acid or sulfuric acid thereto. Thereafter, a reference calibration curve is prepared by measuring the intensity of a standard liquid obtained using a standard solution (5mg / kg) in the inherent wavelength of the Mg element or Li element using an inductively coupled plasma atomic emission spectrometer (ICPAES, Perkin-Elmer 7300). Thereafter, the pretreated sample solution and the blank sample are each introduced into the spectrometer, the actual intensity is calculated by measuring the intensity of each component, the concentration of each component is calculated based on the obtained calibration curve, and then the calculated concentration of multiple components is converted so that the sum of the theoretical value is equal to the calculated concentration, and the content of Mg element or Li element of the prepared silicon-based active material can be analyzed.
[0056] In an exemplary embodiment of the present specification, the carbon layer may be disposed on the surface and / or inside the pores of the silicon-based composite particles. The carbon layer imparts electrical conductivity to the silicon-based composite particles, and the initial efficiency, life characteristics, and battery capacity characteristics of a secondary battery including a negative electrode active material containing the silicon-based composite particles may be improved. Based on a total of 100% by weight of the silicon-based composite particles, the total content of the carbon layer may be 5% to 40% by weight.
[0057] In an exemplary embodiment of the present specification, the carbon layer may include at least one of amorphous carbon and crystalline carbon.
[0058] The average particle size of silicon active materials (D 50 ) may be 2 μm to 15 μm, specifically 3 μm to 12 μm, more specifically 4 μm to 10 μm. When the above range is met, the side reaction between the silicon-based composite particles and the electrolyte solution can be controlled, and the discharge capacity and initial efficiency of the battery can be effectively achieved.
[0059] In this specification, the average particle size (D 50 ) can be defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve. 50 ) can be measured using, for example, the laser diffraction method. In the laser diffraction method, particle sizes from the submicron region to several millimeters can generally be measured, and results with high reproducibility and high resolution can be obtained.
[0060] According to an exemplary embodiment of the present specification, the negative electrode slurry may further include an additional negative electrode active material in addition to the above-mentioned silicon-based active material.
[0061] As an additional negative electrode active material, a compound capable of reversibly inserting and deinserting lithium can be used. Specific examples include: metal materials capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy or Al alloy; metal oxides that can be doped and dedoped with lithium, such as SiOβ (0<β<2), SnO2, vanadium oxide, lithium titanium oxide and lithium vanadium oxide; a composite comprising the above metal materials and a carbonaceous material, such as a Si-C composite or a Sn-C composite; or a carbon-based active material, etc., and any one of them or a mixture of two or more thereof can be used. In addition, a metallic lithium film can be used as a negative electrode active material.
[0062] In an exemplary embodiment of the present invention, a weight ratio of the silicon-based active material to the additional negative electrode active material contained in the negative electrode slurry may be 1:99 to 90:10, specifically 1:99 to 50:50.
[0063] In an exemplary embodiment of the present specification, carbon-based active materials can be used without any particular limitation, and representative examples thereof can include crystalline carbon, amorphous carbon, or a combination thereof. Examples of crystalline carbon include graphite, such as amorphous, plate-like, flaky, spherical, or fibrous natural graphite and artificial graphite, and examples of amorphous carbon include soft carbon (low temperature calcined carbon), hard carbon, mesophase pitch carbide, and fired coke, etc. Graphite can be natural graphite, artificial graphite, or a mixture thereof. Based on 100 parts by weight of all negative electrode active materials contained in the negative electrode active material layer, the content of the carbon-based active material can be more than 60 parts by weight and less than 99 parts by weight.
[0064] In an exemplary embodiment of the present specification, the content of the negative electrode active material in 100 parts by weight of the negative electrode active material layer may be 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and even more preferably 96 parts by weight or more and 99.9 parts by weight or less.
[0065] According to another exemplary embodiment of the present specification, the negative electrode active material layer may further include a negative electrode binder in addition to the silicon-based active material and the carbon-based active material.
[0066] The negative electrode binder can be used to improve the adhesion between the negative electrode active material particles and the adhesion between the negative electrode active material particles and the negative electrode current collector. As the negative electrode binder, those known in the art can be used. Its examples may include polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid and its hydrogen is replaced by Li, Na or Ca etc. At least one of the above-mentioned materials in the group consisting of, and may also include its various copolymers.
[0067] The content of the negative electrode binder may be 0.1 parts by weight or more and 20 parts by weight or less, for example, preferably 0.3 parts by weight or more and 20 parts by weight or less, and more preferably 0.5 parts by weight or more and 10 parts by weight or less, based on 100 parts by weight of the negative electrode active material layer.
[0068] The negative electrode active material layer may not contain a conductive material, but if necessary, it may further contain a conductive material. The conductive material contained in the negative electrode active material layer is not particularly limited as long as the conductive material has conductivity without causing chemical changes in the battery, and for example, graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers, such as carbon fibers or metal fibers; conductive tubes, such as carbon nanotubes; fluorocarbon powders; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and conductive materials such as polyphenylene derivatives, etc. Based on 100 parts by weight of the negative electrode active material layer, the content of the conductive material in the negative electrode active material layer may be 0.01 parts by weight to 20 parts by weight, preferably 0.03 parts by weight to 18 parts by weight.
[0069] In an exemplary embodiment of the present specification, the thickness of the negative electrode active material layer may be 10 μm or more and 500 μm or less.
[0070] In an exemplary embodiment, the negative electrode current collector is not particularly limited as long as it has conductivity without causing chemical changes in the battery. For example, as the current collector, copper, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel treated with carbon, nickel, titanium, silver, etc. on each surface can be used. Specifically, as the current collector, a transition metal (such as copper or nickel) that adsorbs carbon well can be used. The thickness of the current collector can be 1 μm to 500 μm. However, the thickness of the current collector is not limited thereto.
[0071] The positive electrode and the negative electrode can be manufactured by a typical manufacturing method of the positive electrode and the negative electrode, except that the aforementioned positive and negative electrode active materials are used. Specifically, after the composition for forming an active material layer containing the aforementioned active material and an optional binder and a conductive material is applied to the current collector, the electrode is dried and rolled to manufacture the electrode. In this case, the types and contents of the positive and negative active materials, the binder and the conductive material are as described above. The solvent may be a commonly used solvent in the art, such as dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone or water, and any one of them or a mixture of two or more thereof may be used. Considering the coating thickness and preparation yield of the composition, as long as the amount of the solvent can dissolve or disperse the active material, the conductive material and the binder and has a viscosity that can show excellent thickness uniformity in the subsequent coating process of manufacturing the positive and negative electrodes, the amount of the solvent used is sufficient. As another method, the positive and negative electrodes can be manufactured by casting the composition for forming an active material layer on a separate support, and laminating the film obtained by peeling off from the support on the current collector.
[0072] The separator is used to separate the negative electrode from the positive electrode and provide a mobile channel for lithium ions, wherein as a separator, any separator can be used without particular restriction, as long as it is generally used in a secondary battery, and in particular, preferably with a high electrolyte solution water retention capacity and a separator with low resistance to ion movement in the electrolyte. Specifically, a porous polymer film can be used, for example, a porous polymer film formed by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure of more than two layers thereof. In addition, conventional porous non-woven fabrics can also be used, for example, non-woven fabrics made of glass fibers and polyethylene terephthalate fibers with high melting points. In addition, a coated separator including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator with a single layer or multilayer structure can be selectively used.
[0073] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used to prepare lithium secondary batteries, but are not limited thereto.
[0074] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.
[0075] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate or ethyl propionate can be used.
[0076] Particularly, in carbonate organic solvents, ethylene carbonate and propylene carbonate as cyclic carbonate are high viscosity organic solvents, and can be preferably used, because it has high dielectric constant and dissociates lithium salt well.When cyclic carbonate is mixed with low viscosity and low dielectric constant straight chain carbonate (such as dimethyl carbonate and diethyl carbonate) in appropriate ratio and used, electrolyte with high conductivity can be prepared, thus can be more preferably used.
[0077] As the metal salt, a lithium salt can be used. The lithium salt is a material that is easily dissolved in a non-aqueous electrolyte solution. For example, as the anion of the lithium salt, a metal salt selected from the group consisting of F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN -and (CF3CF2SO2)2N - One or more of the groups consisting of.
[0078] For the purpose of improving the service life characteristics of the battery, inhibiting the reduction of the battery capacity, and increasing the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, the electrolyte may further include one or more additives, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glycol dimethyl ether, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidinones, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride.
[0079] Another exemplary embodiment of the present invention provides a battery module including the above-mentioned lithium secondary battery as a unit cell, and a battery pack including the battery module. Since the battery module and the battery pack include secondary batteries with high capacity, high rate capacity and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems.
[0080] Since the secondary battery of the exemplary embodiment of the present invention stably exhibits excellent discharge capacity, output characteristics and cycle performance, the lithium secondary battery can be used as a power source for portable devices such as mobile phones, notebook computers and digital cameras, and medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems. For example, the battery module or battery pack can be used as a power source for one or more of the following medium and large devices: power tools; electric vehicles including electric vehicles (EV), hybrid electric vehicles and plug-in hybrid electric vehicles (PHEV); and power storage systems.
[0081] Example
[0082] Hereinafter, preferred embodiments will be provided to better understand the present invention. It will be apparent to those skilled in the art that these embodiments are only used to illustrate the present invention, and various modifications and changes may be made within the scope and technical spirit of the present invention. Such modifications and changes naturally fall within the scope of the claims included herein.
[0083] Examples 1 to 3
[0084] The positive electrode was prepared by coating, drying and rolling the positive electrode active material layer on the positive electrode current collector. As a composition for preparing the positive electrode active material layer, a nickel-based positive electrode active material (Li 200 mmol / l) having a cobalt oxide layer provided on a portion of the particle surface was prepared at a weight ratio of 97:1:2. 1.0 Ni0.84 Co 0.08 Mn 0.08 O2), a conductive material (CNT) and a binder (PVDF) are added to a methylpyrrolidone (NMP) solvent to prepare a positive electrode slurry (the solid of the positive electrode slurry is included in 70 parts by weight of the entire positive electrode slurry).
[0085] The cathode slurry prepared above was applied onto an Al current collector, which was then dried at a high temperature and roll-pressed at room temperature to prepare a cathode.
[0086] Here, the positive electrode active material includes D having single particles shown in Table 1 below at a weight ratio of 6:4. 50 , tap density and roll density and the first positive electrode active material of the particle strength in Table 2 and having D in Table 2 below 50 and particle strength of the second positive electrode active material.
[0087] The tap density, roll density and pellet strength were measured in the following manner.
[0088] *Tap density: 10 g of each of the positive electrode active materials obtained in Example 1 and Comparative Example 1 was placed in a 300 cc container and then vibrated under certain conditions to measure the apparent density of the resulting particles. Specifically, the tap density of the lithium transition metal oxide particles was measured using a tap density tester (KYT-5000, Seishin).
[0089] *Rolling density: Powder resistance measuring device HPRM-1000 (HAN TECH CO.) was used at 2000kgf / cm 2 The rolling density of the positive electrode active material was measured when the force was rolled (die area: 2.3 cm 2 ).
[0090] *Particle strength: After placing particles on a plate, the force when the particles were broken while increasing the compressive force was measured using a micro compression tester (Shimadzu, MCT-W500), and used as the particle strength value.
[0091] For the negative electrode current collector, a negative electrode slurry (solid content of the negative electrode slurry was 50 parts by weight relative to the whole negative electrode slurry) was prepared by adding a negative electrode active material containing SiO and graphite (containing SiO-based active material in an amount of 5 parts by weight relative to the whole negative electrode active material), a conductive material (carbon black), a binder (SBR) and a thickener (CMC) to a distilled water solvent in a weight ratio of 96:1:2:1.
[0092] The negative electrode slurry prepared above was coated on a Cu current collector, dried at high temperature and roll-pressed at room temperature to prepare a negative electrode.
[0093] The positive electrode and the negative electrode were stacked with a separator inserted therebetween, and an electrolyte solution (1M LiPF6, ethylene carbonate (EC) / ethyl methyl carbonate (EMC) (volume ratio 3 / 7), vinylene carbonate (VC) / propane sultone (PS) (containing 3 parts by weight and 1.5 parts by weight, respectively, based on 100 parts by weight of the electrolyte)) was injected to prepare a lithium secondary battery.
[0094] The electrode density, rolling ratio, and fine powder generation degree of the positive electrode, and the 0.1C efficiency and gas generation degree of the lithium secondary battery are shown in Table 2 below.
[0095] The electrode density, roller compaction ratio, fine powder generation degree and gas generation degree were measured by the following methods.
[0096] *Electrode density: (electrode weight / (electrode thickness*electrode area))
[0097] -Electrode weight: The weight of the slurry excluding the weight of the aluminum foil
[0098] -Electrode thickness: The thickness of the slurry layer excluding the thickness of the aluminum foil
[0099] * Rolling ratio: [(thickness before rolling - thickness of aluminum foil) - (thickness after rolling - thickness of aluminum foil)] / (thickness before rolling - thickness of aluminum foil)
[0100] * Generation of fine powder: For the positive electrode active material obtained by heat-treating the roll-pressed electrode at 500° C. for 5 hours in an air atmosphere, a volume cumulative particle size distribution graph was obtained using Microtrac MT 3000, and then the cumulative volume of 1 μm or less was obtained.
[0101] *Gas generation: The amount of gas generated after the prepared battery was charged to 4.2 V (0.05C cutoff) at 0.33C with constant current / constant voltage (CC / CV) and stored at high temperature (60°C) for 8 weeks was measured using gas chromatography (GC Agilent 7890B).
[0102] Comparative Example 1
[0103] The same procedure as in Example 1 was performed except that secondary particles were used instead of single particles as the first positive electrode active material and single particles having a strength of 149 MPa were used as the first positive electrode active material. The first positive electrode active material as the secondary particle had a secondary particle D of the following Table 1: 50 , tap density and roller density.
[0104] Comparative Example 2
[0105] The same procedure as in Example 1 was performed except that the secondary particles having a strength of 121 MPa were used as the second positive electrode active material and the single particles having a strength of 149 MPa were used as the first positive electrode active material.
[0106] Comparative Example 3
[0107] The same procedure as in Example 1 was performed except that secondary particles having a strength of 121 MPa were used as the second positive electrode active material.
[0108] [Table 1]
[0109]
[0110] As shown in Table 1, it can be confirmed that even when D 50 At the same time, the tap density and roller compaction density of single particles are also higher than those of secondary particles.
[0111] [Table 2]
[0112]
[0113] Since the first positive electrode active materials of Example 1 and Comparative Example 1 are single particles and secondary particles, respectively, the tap density between the first positive electrode active materials is different as shown in Table 1. As a result, the coating thickness of the first positive electrode active material layer coated with the same loading amount before rolling becomes different, resulting in different rolling ratios when rolling to the final target thickness. That is, when a single particle is used as the first positive electrode active material, as in Example 1, the tap density is excellent and the coating thickness of the first positive electrode active material layer is thin, so the rolling ratio when rolling to the target thickness can be improved.
[0114] In Examples 2 and 3, the particle sizes of the first and second positive electrode active materials are the same, but the particle strengths are different compared to Example 1. The second positive electrode active materials of Examples 2 and 3 have different particle strengths from the second positive electrode active material of Example 1, are prepared under different firing conditions from Example 1, and have relatively lower tap densities than the second positive electrode active material of Example 1, so there is a slight difference in rolling ratio.
[0115] As shown in Table 2, it can be confirmed that, in Examples 1 to 3, the generation of fine powder is less, the efficiency is lower, and the generation of gas is greatly reduced, compared with Comparative Examples 1 to 3.
[0116] Comparative Example 1 corresponds to the case of using secondary particles as the first positive electrode active material. Compared with the case of using single particles, it can be confirmed that the tap density is relatively low compared with Examples 1 to 3, so the roll pressing is not properly performed, resulting in more fine powder and gas generation.
[0117] Comparative Examples 2 and 3 correspond to the case where the particle strength of the second cathode active material is less than 150 MPa, and it can be confirmed that the particle strength of the second cathode active material is weak and cracks occur during rolling compared with Examples 1 to 3, resulting in more fine powder and gas generation.
Claims
1. A positive electrode composition comprising: a first positive electrode active material in the form of a single particle; A second positive electrode active material, wherein the particle size of the second positive electrode active material is larger than the particle size of the first positive electrode active material and the particle strength is greater than 150 MPa; Adhesives; and Conductive material.
2. The positive electrode composition according to claim 1, wherein The second positive electrode active material is in the form of secondary particles.
3. The positive electrode composition according to claim 1, wherein The D of the first positive electrode active material 50 The D of the second positive electrode active material is 1 μm to 10 μm. 50 8μm to 20μm.
4. The positive electrode composition according to claim 1, wherein The first positive electrode active material has a tap density of 2 g / cc or more.
5. The positive electrode composition according to claim 1, wherein The first positive electrode active material has a rolling density of 3 g / cc or more.
6. The positive electrode composition according to claim 1, wherein The particle strength of the first positive electrode active material is 150 MPa or more.
7. The positive electrode composition according to claim 1, wherein A weight ratio of the first positive electrode active material to the second positive electrode active material is 1:9 to 9:
1.
8. A positive electrode for a secondary battery, comprising: a current collector; and A positive electrode active material layer is provided on the current collector and comprises the positive electrode composition according to any one of claims 1 to 7.
9. The positive electrode according to claim 8, wherein The fine powder having a particle size of 1 μm or less in the positive electrode active material layer is 5 volume % or less based on 100 volume % of the positive electrode active material layer.
10. A secondary battery comprising: The positive electrode according to claim 8; negative electrode; and Diaphragm.
11. The secondary battery according to claim 10, wherein The negative electrode includes a silicon-based active material.
12. The secondary battery according to claim 11, wherein The negative electrode further comprises a carbon-based active material.
Citation Information
Patent Citations
Imidazoquinoline or benzoindazolone compounds, and intermediates for their manufacture
KR1020220125359A
A Digital Printing Type of a Braille Article with an Antibiotic Property
KR1020230127942A